2006
DOI: 10.1128/jcm.00880-06
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Throat Colonization Is More Frequent than Colonization in the Anterior Nares

Abstract: The aim of this study was to determine the frequency and persistence of Staphylococcus aureus carriage in the throat in relation to anterior naris carriage. By use of a sensitive enrichment broth, S. aureus was cultured from the two sites from 259 patients upon admission to an orthopedic ward and from 87 staff members of the same ward. The throat was the most common carriage site in both groups. Forty percent of the patients and 54% of the staff were positive for S. aureus in the throat, compared to 31% and 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
127
5
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 28 publications
15
127
5
6
Order By: Relevance
“…Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997). Several studies have shown that carriage and colonization in the throat is more common than colonization of the anterior nares (Nilsson & Ripa 2006;Hamdan-Partida et al 2010;Mernelius et al 2013b). It has also been suggested that transmission of S. aureus may occur from the throat although transmission from the anterior nares is more common (Mernelius et al 2013b).…”
Section: Carriage and Colonizationmentioning
confidence: 99%
“…Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997). Several studies have shown that carriage and colonization in the throat is more common than colonization of the anterior nares (Nilsson & Ripa 2006;Hamdan-Partida et al 2010;Mernelius et al 2013b). It has also been suggested that transmission of S. aureus may occur from the throat although transmission from the anterior nares is more common (Mernelius et al 2013b).…”
Section: Carriage and Colonizationmentioning
confidence: 99%
“…Interestingly, post-transplant, S. aureus infection decreased survival, probably because of immunosuppression. Additionally, several recent papers have reported that S. aureus can routinely be obtained from throat cultures of healthy individuals at levels equal to or greater than those found by culturing the anterior nares, thought to be a major reservoir of this organism in most humans [20], suggesting that a positive throat culture for S. aureus from a CF patient might reflect nothing more than what also occurs with this organism in otherwise healthy individuals who are simply S. aureus carriers.H. influenzae has a pathogenic role in patients with non-CF bronchiectasis, but there are no data clearly associating this pathogen with clinical deterioration in CF patients.…”
mentioning
confidence: 99%
“…1 Approximately half of the population are either permanently or transiently colonized by S. aureus in their anterior nares, 2 and a recent report indicates that colonization rates in the throat could be twice as high as in the nares. 3 S. aureus infection is associated with immunocompromised populations, due to either immunodeficiency or to breaches in epidermal barriers, such as surgical incisions or indwelling devices. 4 The observed increase in resistance of these bacteria to different antibacterial compound classes is of great concern, and is compounded by the increased infection rates in populations not traditionally associated with being at risk for S. aureus infection, including prison inmates, sports teams, and men who have sex with men.…”
Section: Introductionmentioning
confidence: 99%